Pembuatan Mural di Sekolah Dasar Kristen Kalam Kudus Kesamben Blitar - Grace Setiati (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
This community service activity in the form of making murals aims to add beauty and provide a new atmosphere for the school environment, especially for children at the Kalam Kudus Blitar Christian Elementary School. The partners wanted the school environment with plain walls to be beautified with murals. The methods implemented are site surveys, material preparation, mural work and activity evaluation. The application of murals in schools does not only prioritize beauty but also educational values according to school age. By incorporating elements of art into the school room, the atmosphere of the room becomes more expressive and becomes a stimulus for creativity for children in carrying out the teaching and learning process. The activity ran smoothly and the partners liked the work they made because the mural created a pleasant learning atmosphere. The impact of this activity for the students of the Interior Design Study Program at Petra Christian University who are involved is that students can develop their creativity in drawing and sharing it with the public. Students also learn about time management and working in teams.